Yugoslavia and Self-Determination of Peoples: The Power to Create and the Power to Destroy - Hrnjaz, Miloš (Journal of Regional Security, 2019)
Over the last hundred years, the terms "Yugoslavia" and "self-determination of peoples" intertwined in numerous ways. Closer inspection reveals that self-determination was important element of the rationale used in a period of establishment of the first and the second Yugoslavia in 1918 and 1945 respectively, and in the course of violent dissolution of SFRY during the last decade of the XX century. This article elaborates on legal status of self-determination in these crucial moments of history of Yugoslav peoples and on the way in which key political figures in Yugoslavia(s) used this principle/right to legitimize their goals. Hence, the article itself is primarily focused on the legitimising role of international law. The way that self-determination was used in the case of Yugoslavia illustrates its great power to influence creation and dissolution of states.